Revisiting cyclophanes: experimental characterization and theoretical elucidation of the chain length influence on their structure and reactivity. (17th March 2022) - Castillo, Francisco; Faúndez, Rodrigo; Tapia, Jorge; Verdugo, Camilo; Preite, Marcelo; Chávez, Ivonne; Manuel-Manriquez, Juan; Ortiz, Pedro D.; Zarate, Ximena; Schott, Eduardo
Abstract : [ n ]Paracyclophanes and dioxa[ n ]paracyclophanes were theoretically studied and synthesized, and it was found that n = 10 was the best candidate and showed improved yields. Abstract : A theoretical study of [ n ]paracyclophanes and dioxa[ n ]paracyclophanes was performed by means of DFT calculations. The geometrical parameters and reactivity indexes were analyzed for chain lengths between 4 and 18 atoms in order to rationalize the best candidates as functional molecules, regarding their major stability. The most stable member of each series, determined through the mentioned theoretical criteria, were synthesized employing improved approaches of previously reported procedures. Hence, better yields were achieved in both cases: from 3% to 8% in the case of (1, 4)-benzenecycloundecaphane, and from 4% to 15% in the case of 2, 11-dioxa-1(1, 4)-benzenecycloundecaphane.